2020
DOI: 10.1371/journal.pone.0228499
|View full text |Cite|
|
Sign up to set email alerts
|

Examining the distributional equity of urban tree canopy cover and ecosystem services across United States cities

Abstract: Examining the distributional equity of urban tree canopy cover (UTCC) has increasingly become an important interdisciplinary focus of ecologists and social scientists working within the field of environmental justice. However, while UTCC may serve as a useful proxy for the benefits provided by the urban forest, it is ultimately not a direct measure. In this study, we quantified the monetary value of multiple ecosystem services (ESD) provisioned by urban forests across nine U.S. cities. Next, we examined the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 84 publications
3
41
0
1
Order By: Relevance
“…School neighborhood poverty level was used to control for neighborhood socio-economic status around schools that may be associated with tree cover, based on a study in one urban area [ 27 ]. While it is unknown whether the school neighborhood poverty level and tree cover is a generalizable relationship [ 33 ], we include it to test whether it is significant with a national sample. School neighborhood poverty was defined as the percent of persons living below the federal poverty line from the American Community Survey 2010–2014.…”
Section: Methodsmentioning
confidence: 99%
“…School neighborhood poverty level was used to control for neighborhood socio-economic status around schools that may be associated with tree cover, based on a study in one urban area [ 27 ]. While it is unknown whether the school neighborhood poverty level and tree cover is a generalizable relationship [ 33 ], we include it to test whether it is significant with a national sample. School neighborhood poverty was defined as the percent of persons living below the federal poverty line from the American Community Survey 2010–2014.…”
Section: Methodsmentioning
confidence: 99%
“…Nesbit and colleagues found that across 10 incorporated cities, neighborhoods with lower education and income had less vegetation, a pattern that was most strongly apparent in large cities [ 28 ]. Riley and Gardiner studied 9 incorporated cities, examining tree cover and ecosystem service provision, which related to socioeconomic variables in different ways in each city [ 29 ]. A similar general trend for inequality in exposure to nature has been observed with remotely sensed measures of greenness [ 30 ], which have been used to analyze vegetation in cities globally [e.g., 31], and with exposure to heat risk due to lack of trees and high impervious cover [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, socio-economic variables are themselves also correlated with aspects of urban form, such as the degree of sprawl and population density [ 43 , 44 ]. Second, some studies have found that the statistical significance of the relationship between tree cover and socioeconomic variables is different if spatial autocorrelation is accounted for [ 27 , 29 ], and one review study observed that studies that controlled for spatial autocorrelation generally found fewer statistically significant trends [ 23 ]. Therefore, one important question when quantifying patterns in tree inequality is whether relationships with socio-economic variables like income and race/ethnicity are statistically significant after accounting for covariates and spatial autocorrelation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst there are exceptions (e.g. Riley & Gardiner, 2020), several reviews (e.g. and empirical studies from different world regions have shown that lower income residential areas within towns and cities are more likely to have the least access to green infrastructure in the form of green spaces or street trees (Astell-Burt & Feng, 2019;McConnachie & Shackleton, 2010;Nero, 2017;Sathyakumar et al, 2019;Shen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%